Elderly Persons with Intellectual Disability: A Study of Clinical Characteristics, Functional Status, and Sensory Capacity - Eli Carmeli; Joav Merrick; Shlomo Kessel; Yossef Masharawi; Varda Carmeli (The Scientific World Journal)
Longer life expectancy is resulting in increasing numbers of elderly adults with intellectual disability (ID). There has been the question whether persons with ID demonstrate early signs of aging before the general population. The aim of this study was to determine if persons with ID (with and without Down syndrome) showed premature aging changes compared with a control group. Elderly persons (n = 24, average age of 61) from one residential care center in Israel and younger adults from another center (n = 37, average age of 45) were compared with elderly residents without ID in an independent living facility. The study considered demographic data, medical data, anthropometric measurements, body fat and body mass index, flexibility, and sensorimotor function tests. The results showed that the persons with ID had basically similar body composition to that of persons without ID, however, the functional performance of elderly adults with ID was more impaired. We postulate that the slower functioning responses may be explained by a less physically active lifestyle, that may accelerate the onset of disease and result in symptoms associated with aging that are detrimental to health. It is therefore important that persons with ID participate in physical activity and exercises in order to promote health and prevent disease.